Molecular cloning and sequence analysis of the Sta58 major antigen gene of Rickettsia tsutsugamushi: sequence homology and antigenic comparison of Sta58 to the 60-kilodalton family of stress proteins. - Stover, C K (1990)
The scrub typhus 58-kilodalton (kDa) antigen (Sta58) of Rickettsia tsutsugamushi is a major protein antigen often recognized by humans infected with scrub typhus rickettsiae. A 2.9-kilobase HindIII fragment containing a complete sta58 gene was cloned in Escherichia coli and found to express the entire Sta58 antigen and a smaller protein with an apparent molecular mass of 11 kDa (Stp11). DNA sequence analysis of the 2.9-kilobase HindIII fragment revealed two adjacent open reading frames encoding proteins of 11 (Stp11) and 60 (Sta58) kDa. Comparisons of deduced amino acid sequences disclosed a high degree of homology between the R. tsutsugamushi proteins Stp11 and Sta58 and the E. coli proteins GroES and GroEL, respectively, and the family of primordial heat shock proteins designated Hsp10 Hsp60. Although the sequence homology between the Sta58 antigen and the Hsp60 protein family is striking, the Sta58 protein appeared to be antigenically distinct among a sample of other bacterial Hsp60 homologs, including the typhus group of rickettsiae. The antigenic uniqueness of the Sta58 antigen indicates that this protein may be a potentially protective antigen and a useful diagnostic reagent for scrub typhus fever.